Bureaucrats and Public Procurement - Dieter Bös (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
This paper deals with a Niskanen type of public-procurement agency. It is shown that the procurement game should be separated into an investment game and a project game, the first game to be played before nature determines the actual realizations of benefit and costs of the project, the second game to be played afterward. In the first game the relationship-specific investments of agency and seller are determined, in the second game the decision on the production of the project is taken. In contrast to many other incomplete-contract papers, in our Niskanen setting it is meaningless to write one and only one contract which refers to both investment and production. Welfare-optimal procurement of the project can be attained under relatively weak assumptions; welfare-optimal investments of the seller (and only of the seller) may result under special circumstances; welfare-optimal investments of both agency and seller cannot be reached.
Keywords: 330; Öffentlicher Auftrag; Unvollständiger Vertrag; Bürokratietheorie; Theorie